2020
DOI: 10.1111/tpj.14643
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary trends in RuBisCO kinetics and their co‐evolution with CO2 concentrating mechanisms

Abstract: Summary RuBisCO‐catalyzed CO2 fixation is the main source of organic carbon in the biosphere. This enzyme is present in all domains of life in different forms (III, II, and I) and its origin goes back to 3500 Mya, when the atmosphere was anoxygenic. However, the RuBisCO active site also catalyzes oxygenation of ribulose 1,5‐bisphosphate, therefore, the development of oxygenic photosynthesis and the subsequent oxygen‐rich atmosphere promoted the appearance of CO2 concentrating mechanisms (CCMs) and/or the evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
136
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(157 citation statements)
references
References 205 publications
3
136
2
Order By: Relevance
“…Additionally, it is likely that some facilitating biochemical elements are also involved in the dynamic regulation of g m , including some aquaporins (Hanba et al, 2004;Flexas et al, 2006Flexas et al, , 2008 and carbonic anhydrases (Momayyezi and Guy, 2017;Guy et al, 2019). Finally, although the different components of photosynthetic photochemistry and biochemistry are sufficiently well known, their complexityinvolving many electron transporters, redox molecules, and soluble enzymes, among other biochemical factors (Anderson, 1975), together with the fact that they are regulate at the transcription and post-transcriptional levels by both nuclear and chloroplastic genes (Fankhausen and Aubry, 2017;Wang et al, 2017;Galm es et al, 2019) overall severely restricts easy manipulation to achieve photosynthetic improvements, although a few successful attempts have been reported (Lefebvre et al, 2005;Raines, 2011;Driever et al, 2017;Simkin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is likely that some facilitating biochemical elements are also involved in the dynamic regulation of g m , including some aquaporins (Hanba et al, 2004;Flexas et al, 2006Flexas et al, , 2008 and carbonic anhydrases (Momayyezi and Guy, 2017;Guy et al, 2019). Finally, although the different components of photosynthetic photochemistry and biochemistry are sufficiently well known, their complexityinvolving many electron transporters, redox molecules, and soluble enzymes, among other biochemical factors (Anderson, 1975), together with the fact that they are regulate at the transcription and post-transcriptional levels by both nuclear and chloroplastic genes (Fankhausen and Aubry, 2017;Wang et al, 2017;Galm es et al, 2019) overall severely restricts easy manipulation to achieve photosynthetic improvements, although a few successful attempts have been reported (Lefebvre et al, 2005;Raines, 2011;Driever et al, 2017;Simkin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Rubisco is a well-studied enzyme in photosynthetic organism since it provides organic carbon for life (Iniguez et al, 2020). Crystal structures of Rubisco from several origins have been analyzed by X-ray, including Rhodospirillum rubrum, Synechococcus PCC6301, Chlorobium tepidum, Thermococcus kodakaraensis KOD1, and so on (Iniguez et al, 2020). Two forms of Rubisco participate in the CBB cycle.…”
Section: Natural Co 2 Fixation Pathwaysmentioning
confidence: 99%
“…As the key enzyme in the CBB cycle, Rubisco is the most abundant protein in the biosphere, which fixes ∼10 11 tons of CO 2 from the atmosphere per year ( Hayer-Hartl and Hartl, 2020 ). Rubisco is a well-studied enzyme in photosynthetic organism since it provides organic carbon for life ( Iniguez et al, 2020 ). Crystal structures of Rubisco from several origins have been analyzed by X-ray, including Rhodospirillum rubrum , Synechococcus PCC6301, Chlorobium tepidum , Thermococcus kodakaraensis KOD1, and so on ( Iniguez et al, 2020 ).…”
Section: Natural Co 2 Fixation Pathwaysmentioning
confidence: 99%
“…This is because prior analyses which did not account for the evolutionary relationships among (and non-independence of) species may have suffered from over-estimated correlation coefficients as a consequence of the phylogenetic co-variation which is observed in kinetic traits (Figure 3A). In order to evaluate the severity by which phylogenetic co-variation may have influenced previous results (Tcherkez, Farquhar and Andrews, 2006; Savir et al , 2010; Flamholz et al , 2019; Iñiguez et al , 2020), the correlations observed in the kinetic trait data using both phylogenetic and non-phylogenetic regression methods were compared (Figure 3B and 3C).…”
Section: Resultsmentioning
confidence: 99%